2010
DOI: 10.1155/2010/412985
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 as a Gatekeeper of Tumor Angiogenesis: Clinical Promise and Potential Pitfalls

Abstract: Tumor vascularization is an essential modulator of early tumor growth, progression, and therapeutic outcome. Although antiangiogenic treatments appear promising, intrinsic and acquired tumor resistance contributes to treatment failure. Clinical inhibition of the molecular chaperone heat shock protein 90 (Hsp90) provides an opportunity to target multiple aspects of this signaling resiliency, which may elicit more robust and enduring tumor repression relative to effects elicited by specifically targeted agents. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 205 publications
1
45
0
Order By: Relevance
“…In the presence of a very few lymphoma cells where HSPH1 is inhibited and Bcl-6 and c-Myc downregulated, the amount of growth factors required to sustain lymphoma engraftment may not be efficiently produced. Because HSPs, 18,19 including HSPH1, 20 sustain tumor neovascularization, and the role c-Myc in promoting this process is well-established, 21,22 we hypothesized that HSPH1 silencing counteracts tumor angiogenesis by multiple sides, thus hampering in vivo engraftment. Quantification of the CD31 1 endothelial area in siHSPH1 and MOCK Namalwa xenografts showed that it was significantly affected by HSPH1 silencing (supplemental Figure 2), thus explaining the differential antilymphoma effects observed in vitro and in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of a very few lymphoma cells where HSPH1 is inhibited and Bcl-6 and c-Myc downregulated, the amount of growth factors required to sustain lymphoma engraftment may not be efficiently produced. Because HSPs, 18,19 including HSPH1, 20 sustain tumor neovascularization, and the role c-Myc in promoting this process is well-established, 21,22 we hypothesized that HSPH1 silencing counteracts tumor angiogenesis by multiple sides, thus hampering in vivo engraftment. Quantification of the CD31 1 endothelial area in siHSPH1 and MOCK Namalwa xenografts showed that it was significantly affected by HSPH1 silencing (supplemental Figure 2), thus explaining the differential antilymphoma effects observed in vitro and in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, bioinformatics also revealed similarities and differences between cancer cell types on the levels of signaling pathways, protein networks, and individual proteins, which has broad implications for the mode of action of the drug in these cells. This is likely also of clinical relevance because the efficacy of HSP90 inhibition varies a lot between tumor entities (10). In fact, up-as well as down-regulation of proteins in response to drug treatment could both be inhibiting (desired) and promoting (undesired) cancer cell survival and proliferation.…”
Section: Hsp90 Regulated Proteome In Different Cellmentioning
confidence: 99%
“…HSF1) (7,8) and, on the other hand, to proteasome mediated degradation of HSP90 substrates (5,9). Experience from clinical trials shows that the efficacy and toxicity of HSP90 targeted therapy varies greatly between tumors suggesting that the current repertoire of client proteins and our understanding of drug mechanism of action is incomplete (10). To predict an individual patient's responsiveness, it would thus be highly desirable to identify the complete set of HSP90 regulated proteins.…”
mentioning
confidence: 99%
“…The angiogenesis cascade is essential and involves key molecules in the progression of cancer (Figure 3). Heat-shock protein 90 (HSP90) is described as a molecular chaperone heavily involved in the regulation of HIF and ultimately impacts significantly on angiogenesis (Bohonowych et al 2010). Apoptosis and angiogenesis in healthy cells are under genetic control, whilst in cancerous cells, mutations in these regulatory genes can lead to out of control cell proliferation and tumour growth through changes in expression levels (Hanahan & Weinberg, 2000).…”
Section: Tumour Growth and Hypoxiamentioning
confidence: 99%